Dehydrogenation of the liquid organic hydrogen carrier system 2-methylindole/2-methylindoline/2-methyloctahydroindole on Pt(111) - Bachmann, Philipp; Steinhauer, Johann; Späth, Florian; Düll, Fabian; Bauer, Udo; Eschenbacher, Roman; Hemauer, Felix; Scheuermeyer, Marlene; Bösmann, Andreas; Büttner, Miriam; Neiß, Christian; Görling, Andreas; et al. (Journal of Chemical Physics, 2019)
Among other N-heterocycles, indole and its substituted derivatives, such as methylindoles, are considered promising Liquid Organic Hydrogen Carriers (LOHCs) for the storage of renewable energy. We used X-ray photoelectron spectroscopy (XPS), temperature programmed desorption (TPD), and density-functional theory (DFT) to investigate the low temperature adsorption and consecutive dehydrogenation reaction during heating of 2-methylindole, 2-methylindoline, and 2-methyloctahydroindole on Pt(111) and their viability as the LOHC system. In the photoemission experiments, for all Hx-2-methylindoles, we find deprotonation at the NH bond starting between 240 and 300 K, resulting in a 2-methylindolide species. Simultaneously or before this reaction step, the dehydrogenation of 2-methyloctahydroindole via 2-methylindoline and 2-methylindole intermediates is observed. For 2-methyloctahydroindole, we also find π-allyl intermediates above 230 K. Starting at ∼390 K, decomposition of the remaining 2-methylindolide species takes place under the conditions of our surface science experiments. DFT calculations give insight into the relative energies of the various species, reaction intermediates, and their isomers both in the gas phase and on the Pt(111) surface.
CRIS-Team Scopus Importer:2019-10-22

Dehydrogenation of the Liquid Organic Hydrogen Carrier System Indole/Indoline/Octahydroindole on Pt(111) - Bachmann, Philipp; Schwarz, Matthias; Steinhauer, Johann; Späth, Florian; Düll, Fabian; Bauer, Udo; Nascimento Silva, Thais; Mohr, Susanne; Hohner, Chantal; Scheuermeyer, Marlene; Wasserscheid, Peter; Libuda, Jörg; et al. (Journal of Physical Chemistry C, 2018)
Indole derivatives are considered as promising liquid organic hydrogen carriers for renewable energy storage. Using X-ray photoelectron spectroscopy, temperature-programmed desorption, and infrared reflection absorption spectroscopy, we investigated low-temperature adsorption and dehydrogenation during heating of indole, indoline, and octahydroindole on Pt(111). For all three molecules, we find deprotonation of the NH bond above 270 K, accompanied with dehydrogenation of indoline and octahydroindole via an indole intermediate, resulting in an indolide species above 300 K. For octahydroindole, we also find a side reaction yielding small amounts of a pi-allyl species between 170 and 450 K. Above 450 K, decomposition of the remaining indolide species takes place.

Homogeneously-catalysed hydrogen release/storage using the 2-methylindole/2-methylindoline LOHC system in molten salt-organic biphasic reaction systems - Soegaard, Alexander; Scheuermeyer, Marlene; Bösmann, Andreas; Wasserscheid, Peter; Riisager, Anders (Chemical Communications, 2019)
Ir-Complex catalysed hydrogen release/storage using a 2-methylindole/2-methylindoline Liquid Organic Hydrogen Carrier (LOHC) system is shown to be effective in a temperature range of 120 to 140 8C. In the form of a liquid-liquid biphasic reaction systemwithmolten [PPh4][NTf2] as catalyst immobilisation phase, the applied cationic Ir-complex can be easily separated and recycled enabling a small amount of ionic catalyst solution to store/release a large amount of hydrogen.
CRIS-Team WoS Importer:2019-02-27

Model Catalytic Studies of Novel Liquid Organic Hydrogen Carriers: Indole, Indoline and Octahydroindole on Pt(111) - Schwarz, Matthias; Bachmann, Philipp; Nascimento Silva, Thais; Mohr, Susanne; Scheuermeyer, Marlene; Späth, Florian; Bauer, Udo; Düll, Fabian; Steinhauer, Johann; Hohner, Chantal; Döpper, Tibor; Noei, Heshmat; et al. (Chemistry - A European Journal, 2017)
Indole derivatives were recently proposed as potential liquid organic hydrogen carriers (LOHC) for storage of renewable energies. In this work, we have investigated the adsorption, dehydrogenation and degradation mechanisms in the indole/indoline/octahydroindole system on Pt(111). We have combined infrared reflection absorption spectroscopy (IRAS), X-ray photoelectron spectroscopy (XPS) and DFT calculations. Indole multilayers show a crystallization transition at 200 K, in which the molecules adopt a strongly tilted orientation, before the multilayer desorbs at 220 K. For indoline, a less pronounced restructuring transition occurs at 150 K and multilayer desorption is observed at 200 K. Octahydroindole multilayers desorb already at 185 K, without any indication for restructuring. Adsorbed monolayers of all three compounds are stable up to room temperature and undergo deprotonation at the NH bond above 300 K. For indoline, the reaction is followed by partial dehydrogenation at the 5-membered ring, leading to the formation of a flat-lying di-sigma-indolide in the temperature range from 330-390 K. Noteworthy, the same surface intermediate is formed from indole. In contrast, the reaction of octahydroindole with Pt(111) leads to the formation of a different intermediate, which originates from partial dehydrogenation of the 6-membered ring. Above 390 K, all three compounds again form the same strongly dehydrogenated and partially decomposed surface species.
Keywords: density functional theory; infrared reflection absorption spectroscopy; liquid organic hydrogen carrier; octahydroindole; X-ray photoelectron spectroscopy

Surface behavior of low-temperature molten salt mixtures during the transition from liquid to solid - Bhuin, Radha Gobinda; Schreiber, Patrick; Heller, Bettina; Scheuermeyer, Marlene; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Molecular Liquids, 2019)
We report on surface investigations of cesium and tetraphenylphosphonium bis(trifluoromethylsulfonyl)imide (Cs[Tf2N], [PPh4][Tf2N]) molten salts and their mixtures. Depending on composition, these ionic compounds combine low melting points with exceptionally high thermal stability, and thus, exhibit considerably enlarged thermal operation windows compared to conventional ionic liquids. To elucidate their liquid-solid transition behavior in the near-surface region, temperature-dependent angle-resolved X-ray photoelectron spectroscopy (ARXPS) investigations were performed using our unique laboratory electron spectrometer DASSA ("Dual Analyzer System for Surface Analysis"), dedicated for investigations of macroscopic liquid samples. We followed temperature-induced changes in bulk and surface composition within the first nanometers of the neat salt melts and of Cs[Tf2N]: (PPh4][Tf2N]= 3 : 1 and 1 : 3 mixtures. In the mixtures, pronounced surface enrichment of Cs+ on expense of the bulky [PPne ions was found in the liquid state at temperatures close to the liquid-solid transition. In the solid state of Cs[Tf2N]-rich mixtures, [PPH4](+) completely vanishes from the near-surface region probed by XPS. (C) 2018 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
CRIS-Team WoS Importer:2019-02-27

Thermally stable bis(trifluoromethylsulfonyl)imide salts and their mixtures - Scheuermeyer, Marlene; Kusche, Matthias Manfred; Agel, Friederike; Schreiber, Patrick; Maier, Florian; Steinrück, Hans-Peter; Davis, James H.; Heym, Florian; Jess, Andreas; Wasserscheid, Peter (New Journal of Chemistry, 2016)
We show that both tetraphenylphosphonium bis(trifluoromethylsulfonyl)imide ([PPh4][NTf2]) and Cs[NTf2] are low melting salts of exceptionally high and also very similar thermal stability. This similarity indicates that the thermal stability is dominated by the anion. Moreover, eutectic mixtures of [PPh4][NTf2] and Cs[NTf2] with melting points below 100 degrees C are presented. Surface analysis of the latter in the liquid state reveals a surprising depletion of (PPh4](+) ions from the surface.